Hypolipidemic Effect of Galoba Fruit (Hornstedtia sp.) Extract on LDL-Cholesterol in Hypercholesterolemic Mice - Nadia Fathiyatur Rahmah; Rachmawati Agustin; Rahmi Latief; Marliyati Sanaky; Vina Zakiah Latuconsina; Sulfiana (Biomedical Journal of Indonesia, 2026)
Introduction. Elevated low-density lipoprotein cholesterol (LDL-C), particularly in its oxidized form, contributes to atherosclerosis and increases the risk of cardiovascular disease. Galoba fruit (Hornstedtia sp.) contains antioxidant phytochemicals that may support lipid regulation. This study evaluated the hypolipidemic effect of Hornstedtia sp. extract in hypercholesterolemic mice. Methods. Twenty-five male mice were randomly assigned to five groups: normal control (KN), negative control (K–, high-fat diet only), positive control (K+, simvastatin 10 mg/kg BW), and two treatment groups receiving Galoba fruit extract at doses of 200 mg/kg BW (P1) and 400 mg/kg BW (P2). Hypercholesterolemia was induced with a high-fat diet, and the extract was prepared by ethanol maceration. Because of limited serum volume, LDL-C levels were estimated indirectly using the Anandaraja equation based on total cholesterol and triglyceride concentrations. Results. LDL-C levels decreased in the extract-treated groups compared with the negative control. The Kruskal–Wallis test showed significant differences among groups (p < 0.05; overall p = 0.000). The greatest reduction was observed in P1 (11.90 mg/dL), followed by P2 (16.60 mg/dL), although neither exceeded the effect of K+ (7.90 mg/dL). Conclusion. Hornstedtia sp. extract demonstrated potential in lowering LDL-C in hypercholesterolemic mice, suggesting its role as a natural adjunct for lipid control. However, the use of indirect LDL-C estimation and the small sample size warrant cautious interpretation. Further studies with direct lipid profiling and mechanistic exploration are recommended before translational application.